A systematic literature review of the policy and practice critiques of higher education exit exams: A global perspective - Teshome, Samson Worku (Rafandha Press, 2025)
Background: Exit exams in higher education have been a subject of extensive debate, with proponents arguing that they ensure quality assurance and accountability, while critics highlight their potential negative impacts on students, educators, and institutions. This systematic literature review aims to synthesize the critiques of exit exams in higher education by analyzing 33 peer-reviewed studies published between 1994 and 2024. Method: The review employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework and PICO (Population, Intervention, Comparison, Outcome) criteria to ensure a rigorous and transparent selection process. A comprehensive search was conducted across multiple databases, including PubMed, ERIC, JSTOR, and Google Scholar, using keywords such as